2006
DOI: 10.1158/0008-5472.can-05-4668
|View full text |Cite
|
Sign up to set email alerts
|

A Novel SV40 TAg Transgenic Model of Asbestos-Induced Mesothelioma: Malignant Transformation Is Dose Dependent

Abstract: Although it has been clear for >40 years that mesothelioma can be caused by asbestos, not all patients with this disease have a history of asbestos exposure. Other factors, including non-asbestos fibers and ionizing radiation, are known to cause malignant transformation of mesothelial cells. In addition, it is likely that genetics will play some role in susceptibility. Recently, it has been suggested that SV40 viral oncogenes could contribute to the carcinogenicity of asbestos. To better understand the role of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 46 publications
(47 reference statements)
7
79
0
Order By: Relevance
“…However, recent studies showed that animals infected with SV40 or transfected with SV40 large T-antigen (TAg) were extremely susceptible to asbestos carcinogenesis, and this is currently used as an in vivo model of SV40 as a co-carcinogen for mesothelioma development [47,48]. A molecular epidemiological study has also indicated a co-carcinogen role of SV40 and studies addressing this question are awaited [49].…”
Section: Ionising Radiation and Mesotheliomamentioning
confidence: 99%
“…However, recent studies showed that animals infected with SV40 or transfected with SV40 large T-antigen (TAg) were extremely susceptible to asbestos carcinogenesis, and this is currently used as an in vivo model of SV40 as a co-carcinogen for mesothelioma development [47,48]. A molecular epidemiological study has also indicated a co-carcinogen role of SV40 and studies addressing this question are awaited [49].…”
Section: Ionising Radiation and Mesotheliomamentioning
confidence: 99%
“…The serum against JCV was kindly provided by E.O. Major (Laboratory of Molecular Medicine and Neuroscience, National Institute of (21) 27 (15) Statistical analysis was performed by the χ 2 test with Yates' correction. No statistically significant differences of SV40 seroprevalence were found between the cohorts of pregnant women and healthy blood donors (P = 0.43) and between the cohorts of subjects exposed to asbestos fibers and healthy blood donors (P = 0.19).…”
Section: Sv40 Mimotopesmentioning
confidence: 99%
“…Indeed, many reports have detected SV40 sequences at high prevalence and the expression of its large tumor antigen (Tag) oncoprotein in MPM. A transforming synergistic action between asbestos fibers and SV40 has been proved in human, hamster, and murine mesothelial cells and in animal models (14)(15)(16).…”
mentioning
confidence: 96%
“…These mice had a higher risk of developing mesothelioma when exposed to asbestos, and the transgenes that contained a higher copy number were at the highest risk (Robinson et al, 2006). Pietruska and Kane (2007) (USA) found that SV40 may contribute to mesothelioma progression by circumventing stress-induced senescence in cells exposed to asbestos in part through p53 inactivation.…”
Section: Pathogenesis: Sv40mentioning
confidence: 99%